Penegakan Hukum Materiel dan Formil Tindak Pidana Pertambangan Emas Tanpa Izin Polda Kalimantan Barat - Meindarwan, Estysaputro; Rahman, Adi Nur (Jurnal Ilmiah Penegakan Hukum, 2025)
This study analyzes the strategies for enforcing both substantive and procedural criminal law by the Directorate of Special Criminal Investigation (Ditreskrimsus) of the West Kalimantan Regional Police in addressing Illegal Gold Mining (PETI), as well as identifying the challenges encountered in the field. The research employs an empirical juridical approach with a socio-legal perspective, conducted through interviews with investigators and analysis of legal documents. The findings indicate that substantive law enforcement is based on Law Number 3 of 2020 concerning Mineral and Coal Mining, while procedural enforcement is carried out through the stages of preliminary inquiry and investigation. However, its implementation faces several obstacles, including geographical constraints, budget limitations, and social resistance from communities economically dependent on PETI activities. The study emphasizes the need for a more integrative law enforcement policy through the harmonization of small-scale mining regulations and inter-agency synergy, recommending the acceleration of the establishment of People’s Mining Areas (WPR) as a strategic solution to reduce legal conflicts and environmental degradation in West Kalimantan.